The Environment and the European Public Sphere Perceptions, Actors, Policies - Wenkel, Christian; Bussiere, Eric; Grisoni, Anahita; Miard-Delacroix, Helene (White Horse Press, 2020)
Addressing the methodological challenge of a European perspective on a transnational subject - one that is commonly distorted by a national prism - this volume shows how perceptions of the environment are increasingly converging and how these convergences of views across political or linguistic borders run exert an influence not only on political debates but also on political decisions across Europe.